The Declared Scientific Ethos of Polish Universities - Czakon, Tomasz (Folia Philosophica, 2021)
The principles that govern the functioning of science and visions of the ethics of scientific research are changing. Many researchers who are examining these changes observe a shift from the academic ethos to the industrial — or “corporate” — ethos. Under the new law on higher education and science, which was passed by the Polish Parliament in 2018, new regulations to the Polish state university system have come into effect. The basic aim of my article has been to examine the scientific ethos in Poland. I based my research on the new statutes adopted by university senates, in which I focused on the value statements and declarations that express the beliefs of university authorities about the most important and desirable model of science. I compared two groups of universities, those which have obtained the status of research universities and colleges from the Upper Silesian Metropolis. My goal was to answer the following questions: 1. What values create the declared ethos of science? 2. What is their hierarchy? 3. To what extent is the ethos of both groups of universities similar? 4. Has the scientific ethos present in the new statutes changed in relation to what was declared earlier? In order to answer these questions, I have applied the technique of document content analysis. My research shows that 1. The ethos of science is changing; 2. The set of declared values in the material under scrutiny is rich and varied.